2015
DOI: 10.1371/journal.pone.0139219
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein Does Not Confer Resistance to Hippocampus-Derived Zpl Cells against the Toxic Effects of Cu2+, Mn2+, Zn2+ and Co2+ Not Supporting a General Protective Role for PrP in Transition Metal Induced Toxicity

Abstract: The interactions of transition metals with the prion protein (PrP) are well-documented and characterized, however, there is no consensus on their role in either the physiology of PrP or PrP-related neurodegenerative disorders. PrP has been reported to protect cells from the toxic stimuli of metals. By employing a cell viability assay, we examined the effects of various concentrations of Cu2+, Zn2+, Mn2+, and Co2+ on Zpl (Prnp -/-) and ZW (Prnp +/+) hippocampus-derived mouse neuronal cells. Prnp -/- Zpl cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…For example, it was reported that PrP C -dependent internalisation of Cu 2+ by cells in culture occurred only when the extracellular Cu 2+ concentration exceeded physiologically relevant levels (Rachidi et al, 2003). Furthermore, although some studies have shown that PrP C expression can protect neuronal and non-neuronal cell lines from oxidative stress caused by excessive Cu 2+ (Rachidi et al, 2003; Watt et al, 2007), Cingaram et al (2015) found that transfecting PrP C into the Zpl hippocampal cell line, originally derived from Zurich I PrP C -knockout mice, did not result in protection from Cu 2+ -mediated toxicity.…”
Section: Prpc Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was reported that PrP C -dependent internalisation of Cu 2+ by cells in culture occurred only when the extracellular Cu 2+ concentration exceeded physiologically relevant levels (Rachidi et al, 2003). Furthermore, although some studies have shown that PrP C expression can protect neuronal and non-neuronal cell lines from oxidative stress caused by excessive Cu 2+ (Rachidi et al, 2003; Watt et al, 2007), Cingaram et al (2015) found that transfecting PrP C into the Zpl hippocampal cell line, originally derived from Zurich I PrP C -knockout mice, did not result in protection from Cu 2+ -mediated toxicity.…”
Section: Prpc Functionmentioning
confidence: 99%
“…Experiments in neuronal cell lines showed that PrP C transfection did not confer protection against the oxidative DNA damage and subsequent cell death caused by treatment with high levels of Mn 2+ , Co 2+ , or Zn 2+ (Watt et al, 2007; Cingaram et al, 2015). However, PrP C expression did protect neuroblastoma cells from the toxic effects of Fe 2+ treatment (Watt et al, 2007).…”
Section: Prpc Functionmentioning
confidence: 99%
“…While the exact physiological function of the prion protein (PrP) is not fully understood, it seems to be a promiscuous protein being involved in several cellular processes and interacting with a great number of partners [1][2][3][4][5][6][7][8]. Nevertheless, PrP is famous for its involvement in devastating neurodegenerative disorders, especially in transmissible spongiform encephalopathies (TSEs), a group of incurable and lethal diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, saturation of recombinant mouse PrP with Cu 2+ has been reported to efficiently enhance conversion to PK-resistant PrP in protein misfolding cyclic amplification (19). Notably, in a previous study, the biochemical features of oxidized PG5, formed via redox, share similarity with Cu 2+ -and Mn 2+ -treated PrP, even with pathological PrP Sc (20). Therefore, it may be hypothesized that, as the propagating substrate for prions, increased oxidation of PrP C may benefit the conversion from PrP C to PrP Sc .…”
Section: Discussionmentioning
confidence: 86%